Population pharmacokinetic and exposure–response analyses of intravenous and subcutaneous rituximab in patients with chronic lymphocytic leukemia. (16th July 2021) - Gibiansky, Ekaterina; Gibiansky, Leonid; Chavanne, Clarisse; Frey, Nicolas; Jamois, Candice
Abstract: A subcutaneous formulation of the anti‐CD20 antibody rituximab has been developed. Fixed‐dose subcutaneous rituximab delivers noninferior serum trough concentrations (Ctrough ), ensuring similar target saturation and comparable efficacy/safety, to intravenous rituximab, but with simplified and shortened preparation and administration. We aimed to characterize the pharmacokinetic (PK) and exposure–response properties of subcutaneous rituximab. Data from two clinical trials were analyzed to describe PKs and pharmacodynamics in patients with chronic lymphocytic leukemia following intravenous and subcutaneous rituximab administration. Intravenous and subcutaneous rituximab were described by a linear two‐compartment population PK model with time‐dependent and time‐independent clearances, and first‐order subcutaneous absorption. Main covariates influencing exposure were body size and baseline white blood cell count. Occurrence of adverse events was not correlated with rituximab exposure. Although greater and more sustainable B‐cell depletion was observed with higher exposure, inherent limitations to the data (use of one dose level, and time‐dependent and target‐impacted PKs) prevented reliable assessment of exposure–response relationships.